Kepemimpinan Imeum Mukim di Kecamatan Seunagan - Rina Melisa (Institut Pemerintahan Dalam Negeri (IPDN), 2016)
Mukim is customary institusiaon and official government agency in the Province of Aceh. The purpose of this research are to describe leadership of imuem mukim in Seunagan Subdistrict Nagan Raya Regional, to describe labor relations subditrict head, imuem mukim and keuchik of governance in Seunagan Subdistrict Nagan Raya Regional, to describe the factors supporting and inhibiting imuem mukim of governance in Seunagan Subdistrict Nagan Raya Regional and to describe the efforts done imuem’s leadership of imuem mukim in Seunagan Subdistrict Nagan Raya Regional. In this research, the writer uses descriptive method with an inductive approach. Sources of data in this research were obtained from the result of classification based on the person, place and paper. Techniques of data collection was conducted by researcher from interviews and documentation. Data analysis is a way of data reduction, data display and conclusion.Based on the research that has been done, it is concluded that leadership in run by imuem mukim ad a leader in Mukim Parom Seunagan Subdistrict has not good implemented. This is because the factors inhibiting greater impact than the factors supporting leadership imuem mukim. Therefore, efforts are needed from imuem mukim of governance in Mukim Parom Seunagan Subdistrict Nagan Raya Regional in the Province of Aceh. Based on these conclusions, the writer suggested for imuem mukim to socialize more about existence Mukim as official government agency in the Province of Aceh for society. The supporting factors imuem mukim managing of government in implementing. Mukim that can be use as a motivation and reference in enhancing leadership qualities. Further efforts in imuem mukim leadership should be good implemented so that many obstacles in managing the mukim of governance can be resolved.